1975
DOI: 10.1677/joe.0.0650319
|View full text |Cite
|
Sign up to set email alerts
|

The Thyroxine-Binding Properties of Serum Proteins. A Competitive Binding Technique Employing Sephadex G-25

Abstract: A competitive binding technique is described for the estimation of the thyroxine (T4)-binding properties of serum proteins in dilute blood serum and lymph. When used in conjunction with an assay for total T4 the following parameters can be estimated: the number of functionally different T4 binding proteins, their individual association constants and binding capacities for T4, the amount of T4 which is bound to each binding species, and the concentration of unbound (free) T4. Both human and sheep serum have thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

1977
1977
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…The fact that there does not exist any significant difference in the distribution volumes or in the a-phase of distribution between the disease-induced sheep and the controls, indicates that there probably exists no important modification in the binding of the thyroxine to the plasma transport proteins. The transport of T 4 and T 3 in sheep is seen to be similar to that of man, Sutherland, Simpson-Morgan (1975) having demonstrated that plasma transport proteins in these animals are similar to human TBG and TBPA. Barzilai, Soloway, Summerskill and Schoenfield (1974) have indicated a reduction in the binding of T 4 to plasma proteins in patients with active chronic hepatopathies.…”
Section: Thyroxine A) Control Studiesmentioning
confidence: 78%
“…The fact that there does not exist any significant difference in the distribution volumes or in the a-phase of distribution between the disease-induced sheep and the controls, indicates that there probably exists no important modification in the binding of the thyroxine to the plasma transport proteins. The transport of T 4 and T 3 in sheep is seen to be similar to that of man, Sutherland, Simpson-Morgan (1975) having demonstrated that plasma transport proteins in these animals are similar to human TBG and TBPA. Barzilai, Soloway, Summerskill and Schoenfield (1974) have indicated a reduction in the binding of T 4 to plasma proteins in patients with active chronic hepatopathies.…”
Section: Thyroxine A) Control Studiesmentioning
confidence: 78%
“…Other methods for the measurement of TBG combine immunological and thyroid hormone-binding techniques, such as those described by Chopra et al (22) and used in the Corning Immophase TBG kit (23). Although STBG was detected in sera of patients with hepatic cirrhosis (2) and more recently was found to be a constituent of normal serum (24), measurements of TBG capacity at saturation have been, in general, consistent with values obtained using immunological techniques (1,6,8,11,13,14,16,17,21). This is not surprising, since native TBG and STBG have identical antigenic determinants, and both have a single binding site for T 4 (2)(3)(4).…”
mentioning
confidence: 70%
“…JCE&M«1984 Vol 59 • No 2 measurement of TBG concentration by immunological techniques. Methods for the estimation of the binding capacity are based on the proportion of isotopically labeled T 4 bound to TBG at a known concentration of total T 4 (8)(9)(10)(11)(12)(13)(14). Immunological techniques for the measurement of TBG include RIAs (15)(16)(17), enzyme immunoassays (18), rocket immunoelectrophoresis (19,20), and radial immunodiffusion (21).…”
mentioning
confidence: 99%
“…The albumin fraction was diluted 1:5 with PBS to lower its salt content. Binding of T4 to albumin was assessed by a modification of the competitive binding technique employing Sephadex G-25 (21). 100 Ml of the diluted albumin fraction was added to several test tubes each containing 200 mg of Sephadex G-25 (medium) preequilibrated with PBS.…”
Section: Binding Studiesmentioning
confidence: 99%
“…Separate experiments were performed in the same range ofT4 concentrations but without serum proteins to estimate T4 binding by Sephadex. The calculation of the albumin-bound T4 was performed according to the original procedure (21), and the binding data were analyzed by the Scatchard method.…”
Section: Binding Studiesmentioning
confidence: 99%